Integrating in-class and online learning activities in a healthcare interpreting course using Moodle. - Maria Tymczyńska (JoSTrans: The Journal of Specialised Translation)
This paper presents and discusses practical ways in which instructors can effectively combine in-class and online learning activities using Moodle, as exemplified by the healthcare interpreting course offered under the Postgraduate Programme in Community Interpreting at Adam Mickiewicz University (AMU), Poznań. It favours a student-centred approach and draws on the social constructivist framework (Duffy & Cunningham 1996; Williams & Burden 1997; Benson 2001; Kiraly 2000, 2003), with instructors acting as "organisers, advisers, and sources of information" (Horváth 2007: 104).